PERSEPSI GURU TENTANG GAYA KEPEMIMPINAN DEMOKRASI KEPALA MADRASAH TSANAWIYAH NEGERI (MTsN) 01 PESISIR SELATAN - Apriadi, Yuda (UIN Imam Bonjol Padang, 2024)
This study aims to determine the category of Teacher Perceptions of the Democratic Leadership Style of the Head of Madrasah Tsanawiyah Negeri (MTsN) 01 South Coast. The method used in this research is quantitativedescriptive to describe the category of Teacher Perceptions of the Democratic Leadership Style of the Head of Madrasah Tsanawiyah Negeri (MTsN) 01 South Coast. The data collection technique is the questionnaire /questionnaire method by distributing closed questionnaires with multiple choice techniques to civil servant teachers. The results of this study indicate that the Democratic Leadership Style of the Head of the madrasa at MadrasahTsanawiyah Negeri (MTsN) 01 Pesisir Selatan is described from the 4 (four) categories of indicators that show in the category quite well with a percentage of 43%. Where the category of each indicator includes: the category of teacher perceptions about decisions made with subordinates in the category is quite good as many as 22 respondents by 63%, the category of teacher perceptions about respecting the potential of each subordinate is in the category is quite good as many as 17 respondents by 49%, the category of teacher perceptions about hearing criticism, suggestions / opinions from subordinates is in the category is not good as many as 14 respondents by 40%, and the category of teacher perceptions about collaborating with subordinates is in the good category as many as 19 respondents by 54%.